A periodicity analysis of the optical variations of 3C 273 - Fan, Jun Hui (2001)
The authors have compiled measurements of N 110 years in the Bband of the quasar 3C 273 and used this database to search for periodicity signals in the optical light curve. Two different methods were applied: the Jurkevich method and the discrete correlation function (DCF) method. They revealed the existence of periods of 2.0, (13.65 f 0.20) and (22.50 f 0.20)yr in the source variability. Possible origin of such a variability is discussed.